2022
DOI: 10.1002/uog.24861
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of placenta accreta spectrum in high‐risk women using ultrasonography or magnetic resonance imaging: systematic review and meta‐analysis

Abstract: What are the novel findings of this work?Our findings show that ultrasound and magnetic resonance imaging (MRI) have similar sensitivity and specificity for the diagnosis of placenta accreta spectrum (PAS) in high-risk women. However, the meta-analysis was complicated by heterogeneous subsets of women and methodology across studies. What are the clinical implications of this work?Our systematic review included studies focusing on women who had undergone both MRI and ultrasound examinations, allowing a direct c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…5 In high-risk cohorts, MRI may be equivalent to ultrasonography in diagnostic accuracy. 48 However, caution is warranted in interpreting these data because MRI research for PAS is typically performed in busy referral centers and only in patients who have very high suspicion for PAS based on ultrasonography.…”
Section: Diagnosismentioning
confidence: 99%
“…5 In high-risk cohorts, MRI may be equivalent to ultrasonography in diagnostic accuracy. 48 However, caution is warranted in interpreting these data because MRI research for PAS is typically performed in busy referral centers and only in patients who have very high suspicion for PAS based on ultrasonography.…”
Section: Diagnosismentioning
confidence: 99%
“…De Oliveira Carniello et al [ 18 ▪▪ ] performed a systematic review and meta-analysis of the diagnostic test accuracy of ultrasound and MRI, also comparing the performance of the two techniques in the diagnosis of PAS. They included observational studies evaluating diagnostic accuracy in women with risk factors for PAS who had undergone both ultrasound and MRI.…”
Section: Magnetic Resonance Imaging Diagnosismentioning
confidence: 99%
“…According to previous meta‐analyses, the accuracy of ultrasound for diagnosing PAS ranges from 83% to 95% in experienced centers 15,16 . However, studies have shown that the accuracy of diagnosing PAS disorders depends on operator experience, which may be limited in some tertiary centers 16–18 . with a previous study reporting moderate interobserver variation (κ = 0.47) 19 .…”
Section: Introductionmentioning
confidence: 96%